Diversidade de bactérias endofíticas de raízes de milho (Zea mays L.) e potencial para promoção de crescimento - Cerigioli, Márcia Maciel (2005)
Due to the ever-increasing amounts of nitrogenous and phosphates fertilizers which are used for crop production, the great energy need for the production of these, and to the environmental impact provoked by the lixiviate, it is becoming very important to try to extend biological nitrogen fixation to nonlegume, as well as the use of the solubilization of inorganic phosphate of reservations of the soil for the bacterias turning it available the plants in general. It is also important the understanding of the interaction bacteria-plant in the production of the auxin IAA and your use in the increase of the crop production, besides the knowledge of the diversity of endophytic bacterias for a possible use of the same in several ways, due to your adaptation to the internal conditions of the plants. This way, this work had as objectives to study the diversity of bacterias endofíticas in the culture of the corn (Zea mays) and to select endophytic with potential for the growth promotion and your activity in the plant. This work had as objectives study the diversity of endophytic bacterias in the culture of maize (Zea mays) and to select of their plant-growth promoting potential and activity in the plant. The diversity was evaluated in plants collected at four places of the State of São Paulo and the identification was performed by the fatty acids method extraction (FAME). A great number of bacterias was isolated where the difference can be observed in the diversity in relation to the places. The largest diversity of species was observed at the place of Lins. The group Proteobacteria prevailed in the endophytic bacterial communities being the γ- subdivision and in the Enterobacteriaceae Famíly the most frequent and with larger diversity. The most frequent genus were Stenotrophomonas and Bacillus. The populations endophytic maize present characteristics related to the plant growth promotion as, production of IAA, nitrogen fixation, and to solubilize phosphate. The different cultivation conditions and genotypes, as well as of developmental stage they might have influenced the observed physiologic diversity. Endophytic bacterias belonging to the species Klebsiella pneumoniae, Microbacterium saperdae, Stenotrophomonas maltophilia, Enterobacter cloacae, Bacillus megaterium and Pseudomonas mucidolens promoted the increase of root weight and of the aerial part of maize plants, presenting to application potential.